SFL ANALYSIS: AN INVESTIGATION OF STUDENTS' USE OF COHESIVE DEVICES IN EXPOSITION TEXT - Alfath Eka Liani, - (2021)
Cohesively composing text is crucial in the context of academic writing, especially when it comes to analytical exposition text; hence, mastering and understanding how to utilise cohesive devices in analytical exposition text becomes critical. For that reason, this study aims to investigate how students utilise cohesive devices in analytical exposition text and to find out its inaccurate uses. By employing Qualitative Content Analysis (QCA) as the method, this study examines the realisation of cohesive devices in 11th grade senior high school students' analytical exposition text. Ranging from low, middle to high achieving level, as many as six texts were analysed using Halliday and Hasan's 1976 cohesion framework. This study was conducted at one of Indonesian public senior high schools located in Cimahi. This study reveals lexical cohesion as the most dominant cohesive devices utilised in the students' texts followed by reference and conjunction. Moreover, inaccurate uses of cohesive devices were also identified with the majority of reference and conjunctions being misused and repetition being redundantly utilised. These signal that although the students are skilful in presenting relevant information and evidence as well as making their texts identifiable and personal, they still lack interlingual and intralingual skill, lack exposure to the English language and experience confusion in employing cohesive devices. Thus, it is obligatory for teachers to equip them with adequate knowledge concerning text cohesiveness as well as provide more practice and feedback to train students' skill in language transfer.